KAJIAN PROSES DAN ANALISIS KELAYAKAN FINANSIAL USAHA UBI CILEMBU BAKAR - Ahmad Thoriq; Asri Widyasanti (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2019)
Cilembu sweet potato are local superior varieties from Cilembu Village, Sumedang District, West Java. Sweet taste like honey is produced through the process of planting at a certain height, ripening after post-harvest, and baked using an oven. The policy of converting fuel oil to gas fuel has implications for the baking of Cilembu yams which previously used Liquified Petroleum Gas (LPG) ovens. But along with the limited availability and the high price of kerosene demanding the modification of the grill oven using Liquified Petroleum Gas. This study aims to conduct a process study and analyze the financial feasibility business of cilembu sweet potato baking. The method used in this study is an experimental method that was collaborated with descriptive methods to analyze the financial feasibility of cilembu sweet potato baking. The results showed that the average temperature of the baking room was 138 0C, effective baking capacity of 6.64 kg / hour, consumption rate of LPG 0.44 kg / hour, rate of decrease in average weight of Cilembu sweet potato during the baking process of 5.66 grams per minutes for grade C and 3.68 grams per minute for grade B with yields of cilembu sweet potato baking produced at 77.38% and loss weights of 22.62%. Based on the financial feasibility analysis obtained HPP Rp. 14,132.72 / kg, NPV Rp. 73,154,539 / month, BCR 1.28, IRR 20.06% and capital will return in the eighth month.